DHL and facilitating small business trade - Baack, Daniel W., (SAGE knowledge. Cases., 2016)
This case study tracks the growth of DHL, from a small courier between California and Hawaii, to an international shipping organization. In more recent years, DHL has directed focus to facilitating trade for small and medium businesses in emerging markets, and this case investigates the various strategies by which these markets are reached.